A comparison between different approaches for modelling media with viscoelastic properties via optimization analyses. Issue 5 (30th November 2016) - Lekszycki, Tomasz; Bucci, Sara; Del Vescovo, Dionisio; Turco, Emilio; Rizzi, Nicola Luigi
Abstract : The authors deal with the problem of choosing the best linear model capable to describe the mechanical characteristics and the behavior of media with viscoelastic properties. Two different cases are studied: asphalt concrete subject to forced vibrations and PVC cantilever beam subject to free vibrations. In both cases, experimental results are compared with specific models and the identification of the most suitable one is carried out with the help of optimization theories, namely the minimization of an objective function, the Kalaman filtering or the Bland and Lee approach. Abstract : In this paper we deal with the problem of choosing the best linear model capable to describe the mechanical characteristics and the behavior of media with viscoelastic properties. Two different cases are studied: asphalt concrete subject to forced vibrations and PVC cantilever beam subject to free vibrations. In both cases, experimental results are compared with specific models and the identification of the most suitable one is carried out with the help of optimization theories, namely the minimization of an objective function, the Kalaman filtering or the Bland and Lee approach.